Wet nonwoven fabric for filter, filter obtained by using the same and method for manufacturing the filter

The wetlaid nonwoven fabric, composed of polyester fibers with isophthalic acid and/or sulfoisophthalic acid salt, addresses the issues of strength and chemical resistance in filter substrates, ensuring robustness during aprotic solvent exposure and porous membrane formation.

JP2025147636APending Publication Date: 2025-10-07TEJIN FIBERS LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024047982
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-03-25
Publication Date
2025-10-07

AI Technical Summary

Technical Problem

Existing nonwoven fabrics for filters lack sufficient strength and chemical resistance, particularly when exposed to aprotic solvents during porous membrane formation, and are prone to deformation or damage during processing.

Method used

A wetlaid nonwoven fabric made of synthetic fibers, primarily containing polyester unstretched staple fibers with 2 to 18 mol% isophthalic acid and/or sulfoisophthalic acid salt, combined with drawn polyester fibers, providing enhanced strength and chemical resistance.

Benefits of technology

The nonwoven fabric achieves high strength and excellent chemical resistance, maintaining integrity during aprotic solvent exposure and porous membrane formation, resulting in a robust filter substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025147636000001
    Figure 2025147636000001
  • Figure 2025147636000002
    Figure 2025147636000002
  • Figure 2025147636000003
    Figure 2025147636000003
Patent Text Reader

Abstract

To provide a nonwoven fabric for a filter, the nonwoven fabric having sufficient strength and furthermore having excellent chemical resistance, and to provide a filter obtained by using the nonwoven fabric.SOLUTION: A wet nonwoven fabric for a filter is provided, which is composed of synthetic fiber and includes polyester undrawn staple fibers containing 2-18 mol% of isophthalic acid and / or sulfoisophthalate, and has a basis weight of 30-400 g / m2. Further, it is preferable that the wet nonwoven fabric has drawn fibers as main fibers and that the drawn fibers are polyester drawn fibers. The filter of the present invention is comprised of the wet nonwoven fabric for the filter and a porous membrane present on the surface thereof. Further, it is preferable that the porous membrane is composed of any one of polysulfone, polyethersulfone or polyvinylidene fluoride and further has an aromatic polyamide layer on its surface. Further, a method for manufacturing a filter using an aprotic polar solvent when forming a porous membrane is included in the present invention.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a nonwoven fabric suitable for use in filters, particularly as a substrate for filters, a filter using the nonwoven fabric, and a method for producing the same. [Background technology]

[0002] Nonwoven fabrics for filters include those in which the nonwoven fabric itself is primarily responsible for the filtering effect, and those in which the nonwoven fabric itself serves as a support, with a porous membrane or the like formed on the surface of the support, with the separation function being primarily performed by the porous membrane and the nonwoven fabric primarily providing strength.

[0003] For example, Patent Document 1 uses a substrate made of a heat-treated nonwoven fabric made of composite fibers with a polypropylene core and a polyethylene sheath. However, while this material has excellent alkali resistance, it is inferior to the various chemicals used to form porous membranes. Furthermore, it has poor heat resistance, making it difficult to handle during processing. Patent Document 2 proposes a nonwoven fabric made by thermocompressing a spunbonded nonwoven fabric with a heated metal roll. However, spunbonded nonwoven fabrics have a variation in fiber diameter, and the fine fibers inevitably present reduce the chemical resistance of the entire nonwoven fabric. Another problem is that the fibers are easily crushed during metal roll processing, making it difficult to maintain a high porosity. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Laid-Open No. 2001-17842 [Patent Document 2] International Publication No. 2015 / 046215 Brochure Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a nonwoven fabric for filters that has sufficient strength and excellent chemical resistance, and a filter using the same. [Means for solving the problem]

[0006] The wetlaid nonwoven fabric for filters of the present invention is a wetlaid nonwoven fabric made of synthetic fibers, which contains polyester unstretched staple fibers containing 2 to 18 mol % of isophthalic acid and / or sulfoisophthalic acid salt, and has a basis weight of 30 to 400 g / m 2 It is characterized in that:

[0007] Furthermore, it is preferable that the wetlaid nonwoven fabric contains drawn fibers as the main fibers, that the drawn fibers are drawn polyester fibers, and that the maximum peak height in the surface roughness of the wetlaid nonwoven fabric is in the range of 0.05 to 100 μm.

[0008] Another filter of the present invention is a filter comprising any one of the above wetlaid nonwoven fabrics for filters and a porous membrane present on the surface thereof. Furthermore, it is preferable that the porous membrane is made of polysulfone, polyethersulfone, or polyvinylidene fluoride, and further has an aromatic polyamide layer on the surface thereof.

[0009] The present invention also encompasses a method for producing a filter, which comprises forming a porous membrane on the surface of any of the above-mentioned wetlaid nonwoven fabrics for filters, and preferably further comprises using an aprotic polar solvent when forming the porous membrane. [Effects of the Invention]

[0010] According to the present invention, there are provided a nonwoven fabric for filters having sufficient strength and excellent chemical resistance, a filter using the same, and a method for producing the same. DETAILED DESCRIPTION OF THE INVENTION

[0011] The present invention will be described in detail below. The wetlaid nonwoven fabric for filters of the present invention is a wetlaid nonwoven fabric made of synthetic fibers, which contains polyester unstretched staple fibers containing 2 to 18 mol % of isophthalic acid and / or sulfoisophthalic acid salt, and has a basis weight of 40 to 400 g / m 2 It is a nonwoven fabric.

[0012] Here, as the synthetic fibers, fibers made of various synthetic resins used for filters can be used, but synthetic fibers made of polyester resin (polyester fibers) that are particularly excellent in chemical resistance and strength are preferred.

[0013] The polyester fiber preferably used in the present invention is a fiber formed mainly from polyester resin, and preferably contains 50 mol % or more, and particularly preferably 80 mol % or more of polyester resin.

[0014] More specifically, examples of polyester resins preferably used in the present invention include polyesters of aromatic dicarboxylic acids and aliphatic diols, such as polyalkylene terephthalates, such as polyethylene terephthalate, polytrimethylene terephthalate, or polybutylene terephthalate (polytetramethylene terephthalate), or polyalkylene naphthalates, such as polyethylene naphthalate, polytrimethylene naphthalate, or polybutylene naphthalate (polytetramethylene naphthalate). Alternatively, fibers made of polyesters obtained from alicyclic dicarboxylic acids and aliphatic diols, such as polyalkylene cyclohexane dicarboxylate, polyesters obtained from aromatic dicarboxylic acids and alicyclic diols, such as polycyclohexanedimethylene terephthalate, polyesters obtained from aliphatic dicarboxylic acids and aliphatic diols, such as polyethylene succinate, polybutylene succinate, or polyethylene adipate, or polyesters obtained from polyhydroxycarboxylic acids, such as polylactic acid or polyhydroxybenzoic acid, may also be used. Furthermore, preferred examples of resins that can be used for polyester fibers include copolymers and blends of these polyester components in any ratio, and also include mixtures of polyesters with different compositions as exemplified above.

[0015] Among these, the polyester fibers preferably used in the present invention are fibers made of polyalkylene terephthalate resin or polyalkylene naphthalate resin, in view of their good physical properties and ease of handling.

[0016] The synthetic resin that becomes the fiber may contain known additives such as pigments, dyes, matting agents, antifouling agents, antibacterial agents, deodorizers, fluorescent whitening agents, flame retardants, stabilizers, ultraviolet absorbers, and lubricants.

[0017] The wetlaid nonwoven fabric for filters of the present invention is made of synthetic fibers, and preferably contains drawn fibers as part of the synthetic fibers, resulting in a nonwoven fabric with excellent strength. Furthermore, for the wetlaid nonwoven fabric of the present invention, it is also preferable that the drawn fibers are the main fibers. Here, the main fibers are the fibers that provide the majority of the strength of the nonwoven fabric, and are preferably the fibers with the highest content, more preferably 35% by weight or more, and particularly preferably 55 to 95% by weight.

[0018] Furthermore, the synthetic fibers used in the wetlaid nonwoven fabric for filters of the present invention are preferably short fibers, with a fiber length of preferably 1 to 20 mm, more preferably 3 to 15 mm, and particularly preferably 5 to 12 mm. If the fiber length is too long, the fibers will become entangled in water, reducing dispersibility in water and increasing the number of defects in the wetlaid nonwoven fabric. If the fiber length is too short, the fibers will not intertwine easily, reducing the strength of the nonwoven fabric.

[0019] The cross-sectional shape of the synthetic fibers is not particularly limited, but when strength is important, a round cross section is preferable. The single fiber fineness is preferably 0.1 to 3.0 dtex, more preferably 0.3 to 2.0 dtex, and particularly preferably 0.3 to 1.7 dtex. If the single fiber fineness is too large, the number of fibers in the nonwoven fabric will be small, and the strength of the nonwoven fabric will tend to decrease. If the single fiber fineness is too small, the number of fibers in the nonwoven fabric will be too large, and they will not be fixed by the binder fiber, and the fluff on the surface of the nonwoven fabric will tend to increase.

[0020] The wetlaid nonwoven fabric for filters of the present invention is made of the above-mentioned synthetic fibers, but it is essential that it further contains polyester unstretched short fibers containing 2 to 18 mol % of isophthalic acid and / or sulfoisophthalic acid salt.

[0021] The polyester resin used for this polyester unstretched staple fiber can be any of the various polyester resins preferably used for the above-mentioned synthetic fibers. Among them, the polyester resin preferably used for the polyester unstretched staple fiber used in the present invention is preferably a polyalkylene terephthalate resin or a polyalkylene naphthalate resin because of their good physical properties and ease of handling. Furthermore, this polyester may contain known additives such as pigments, dyes, matting agents, antifouling agents, antibacterial agents, deodorizers, fluorescent whitening agents, flame retardants, stabilizers, ultraviolet absorbers, lubricants, etc.

[0022] These unstretched polyester staple fibers contain 2 to 18 mol% of isophthalic acid and / or sulfoisophthalic acid salt as copolymerization components in the polyester resin constituting the fibers. The inclusion of these copolymerization components in these unstretched polyester staple fibers allows for both high binder performance and chemical resistance. Furthermore, it also enables further improved chemical resistance to aprotic solvents used in subsequent filter manufacturing processes. If the copolymerization component of isophthalic acid and / or sulfoisophthalic acid salt is less than 2 mol%, the binder performance is insufficient and the strength of the nonwoven fabric decreases. On the other hand, if it exceeds 18 mol%, the chemical resistance decreases and the nonwoven fabric deforms, especially during porous membrane production using aprotic solvents, which is undesirable. A more preferred range is 3 to 16 mol%, and an even more preferred range is 4 to 15 mol%.

[0023] In the undrawn polyester staple fibers used in the present invention, in addition to the essential isophthalic acid and / or sulfoisophthalic acid salt components, the following dicarboxylic acid components may be used to form the polyester: phthalic acid, alkali metal salts of 5-sulfoisophthalic acid, quaternary ammonium salts of 5-sulfoisophthalic acid, quaternary phosphonium salts of 5-sulfoisophthalic acid, succinic acid, adipic acid, suberic acid, sebacic acid, cyclohexanedicarboxylic acid, α,β-(4-carboxyphenoxy)ethane, 4,4-dicarboxyphenyl, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, or diester compounds thereof having an organic group having 1 to 10 carbon atoms, which may be copolymerized as one component or two or more components. Similarly, the diol component constituting the polyester may be one or more copolymerized components such as diethylene glycol, 1,2-propanediol, 1,2-butanediol, 1,3-butanediol, 1,6-hexanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, 2,2-bis(p-β-hydroxyethylphenyl)propane, polyethylene glycol, poly(1,2-propylene) glycol, poly(trimethylene) glycol, or poly(tetramethylene) glycol. Furthermore, branched polyesters obtained by copolymerizing one or more components of hydroxycarboxylic acids such as ω-hydroxyalkylcarboxylic acids, pentaerythritol, trimethylolpropane, trimellitic acid, or trimesic acid, or compounds containing three or more carboxylic acids or hydroxyl groups, are also preferred. Furthermore, mixtures of the above-listed polyesters with different compositions may also be used.

[0024] The amount of copolymerization of the polyester unstretched short fibers used in the present invention is preferably adjusted so that the amount of dissolution in the aprotic solvent is 10% by mass or less. If the amount of dissolution is too large, the binder fibers in the nonwoven fabric will dissolve when the porous membrane is subsequently applied to the nonwoven fabric, and wrinkles will be likely to occur frequently on the surface of the porous membrane. The amount of dissolution in the aprotic solvent is more preferably 9% by mass or less, and particularly preferably within the range of 7% to 0.1% by mass.

[0025] The polyester undrawn short fibers used in the present invention can be produced, for example, by the following method. Specifically, the pelletized copolymer polyester resin is dried by conventional methods, melt-spun in a spinning facility equipped with a screw extruder and spinneret, cooled and solidified, and then taken up at a speed of 100 to 2,000 m / min. It is important that the spinning process does not involve a drawing step. Furthermore, the spinneret may not only be a single-hole type, but also a spinneret that uses two or more resins, such as a core-sheath type, side-by-side type, segment pie type, or sea-island type composite fiber. The resulting polyester fibers are bundled and fed to a cutter while retaining 5 to 40% by mass of moisture, where they are cut to the desired fiber length to produce short fibers.

[0026] The shape of the undrawn polyester staple fibers used in the present invention is not limited to a round cross section, and may be an elliptical cross section, a multilobal cross section such as a 3- to 8-lobal cross section, or a non-circular cross section such as a polygonal cross section having 3 to 8 sides, etc. However, from the viewpoint of strength, it is preferable that the outer periphery of the cross section is a round cross section, and in that case, the fibers may be either solid or hollow.

[0027] The single filament fineness of the unstretched short fibers is preferably 0.01 to 2.0 dtex, more preferably 0.3 to 1.7 dtex, and particularly preferably 0.5 to 1.5 dtex. If the single filament fineness is too large, the number of binder fibers in the nonwoven fabric tends to decrease, resulting in a decrease in the strength of the nonwoven fabric. If the single filament fineness is too small, stable fiber production tends to become difficult.

[0028] The fiber length of the unstretched short fibers is preferably 1 to 20 mm, more preferably 3 to 15 mm, and particularly preferably 4 to 12 mm. If the fiber length is too long, the fibers will become entangled in water during the wetlaid nonwoven fabric production process, which will tend to reduce dispersibility in water and increase defects in the wetlaid nonwoven fabric. If the fiber length is too short, the fibers will not intertwine easily, which will tend to reduce the strength of the wetlaid nonwoven fabric.

[0029] The intrinsic viscosity of the unstretched short fibers used in the present invention is preferably in the range of 0.30 to 0.65 dL / g, more preferably 0.34 to 0.58 dL / g, and even more preferably 0.35 to 0.57 dL / g. If the intrinsic viscosity is too low, the strength of the fibers tends to decrease and fiberization tends to become difficult. On the other hand, if the intrinsic viscosity is too high, the binder performance tends to decrease.

[0030] The birefringence of the unstretched short fibers is preferably 0.005 to 0.05, more preferably 0.006 to 0.01, and even more preferably 0.007 to 0.01. If the birefringence is too low, the strength of the fibers tends to decrease and fiberization tends to become difficult. On the other hand, if the birefringence is too high, the binder performance tends to decrease.

[0031] The specific gravity of the unstretched short fibers is preferably 1.32 to 1.36, and more preferably 1.34 to 1.35. If the specific gravity is too low, the strength of the fibers tends to decrease and fiberization tends to become difficult. On the other hand, if the specific gravity is too high, the binder performance tends to decrease.

[0032] The crystallization onset temperature of the unstretched short fibers is preferably 105 to 129°C, more preferably 110 to 125°C, and even more preferably 115 to 125°C. If the crystallization onset temperature is too low, crystallization tends to proceed easily during papermaking, resulting in a decrease in binder performance. On the other hand, if the crystallization onset temperature is too high, the fibers tend to be easily dissolved in aprotic solvents.

[0033] The crystallization peak temperature of the unstretched short fibers is preferably 124 to 160°C, more preferably 130 to 150°C, and even more preferably 130 to 145°C. If the crystallization peak temperature is too low, crystallization tends to proceed easily during papermaking, resulting in a decrease in binder performance. On the other hand, if the crystallization peak temperature is too high, the fibers tend to be easily dissolved in aprotic solvents.

[0034] The wetlaid nonwoven fabric made of synthetic fibers of the present invention must contain the above-mentioned polyester unstretched staple fibers, but as other synthetic fibers, those containing stretched fibers as the main fiber are preferred as described above, and among these, it is preferred that the stretched fibers are polyester stretched fibers. In particular, it is preferred that the wetlaid nonwoven fabric be made of polyester unstretched staple fibers and polyester stretched staple fibers.

[0035] The polyester drawn staple fibers preferably used in the present invention will now be described in more detail. As examples of polyesters used for oriented polyester staple fibers, polyesters of aromatic dicarboxylic acids and aliphatic diols can be mentioned, as with the polyesters described above for synthetic fibers. Further preferred examples include copolymers and blends of these polyester components in any ratio, which may contain known additives such as pigments, dyes, matting agents, antifouling agents, antibacterial agents, deodorizers, fluorescent whitening agents, flame retardants, stabilizers, ultraviolet absorbers, lubricants, etc.

[0036] Among these, the polyester resin preferably used in the present invention is a polyalkylene terephthalate resin or a polyalkylene naphthalate resin, because of their excellent physical properties and ease of handling.

[0037] The drawn short fibers used in the present invention are produced by a known method and are synthetic fibers obtained by drawing undrawn fibers after spinning to develop fiber strength and then cutting them into short lengths. The cross-sectional shape of the fibers is not particularly limited, but when strength is important, a round cross section is preferred.

[0038] The intrinsic viscosity of the drawn fiber is preferably 0.55 to 0.70 dL / g, more preferably 0.55 to 0.68 dL / g, and even more preferably 0.58 to 0.65 dL / g. If the intrinsic viscosity is too low, the strength of the fiber tends to decrease, and the tensile strength of the nonwoven fabric tends to decrease. On the other hand, if the intrinsic viscosity is too high, fiberization tends to become difficult.

[0039] The single filament fineness of the drawn staple fibers is preferably 0.1 to 3.0 dtex, more preferably 0.3 to 2.0 dtex, and particularly preferably 0.3 to 1.7 dtex. If the single filament fineness is too large, the number of fibers in the nonwoven fabric will be small, and the strength of the nonwoven fabric will tend to decrease. If the single filament fineness is too small, the number of fibers in the nonwoven fabric will be too large, and the fibers will not be fixed by the binder fibers, and the fluff on the surface of the nonwoven fabric will tend to increase.

[0040] The fiber length of the drawn short fibers is preferably 1 to 20 mm, more preferably 3 to 15 mm, and particularly preferably 4 to 12 mm. If the fiber length is too long, the fibers will become entangled in water, reducing dispersibility in water and increasing the number of defects in the wetlaid nonwoven fabric. If the fiber length is too short, the fibers will not intertwine easily, reducing the strength of the nonwoven fabric. The wetlaid nonwoven fabric for filters of the present invention is a wetlaid nonwoven fabric made of synthetic fibers including unstretched polyester staple fibers as described above.

[0041] The wetlaid nonwoven fabric will now be described in more detail. The wetlaid nonwoven fabric preferably contains particularly drawn staple fibers (main fibers) and polyester-based undrawn staple fibers, and the details of each fiber are as described above.

[0042] Such a wetlaid nonwoven fabric of the present invention can be produced by a known papermaking process. For example, fibers may be dispersed in a pulper, followed by multi-layer papermaking using a fourdrinier papermaking method, a cylinder papermaking method, a short wire papermaking method, or a combination of these methods. To obtain a more uniform wetlaid nonwoven fabric, a dispersant or an antifoaming agent may be added to the pulper. Specific examples of dispersants include DT-100 (Takamatsu Yushi Co., Ltd.).

[0043] The mass ratio of the polyester unstretched staple fibers that serve as binder fibers in the wetlaid nonwoven fabric is preferably 5% or more, more preferably 20 to 70%, and even more preferably 30 to 60%. If the amount of binder fiber is too small, adhesion will be insufficient, and the strength of the wetlaid nonwoven fabric will tend to be low. In addition to the polyester unstretched staple fibers, other binder fibers can also be used in combination.

[0044] The drying process after papermaking is carried out according to conventional methods using a Yankee dryer, air-through dryer, or the like. The drying temperature is preferably in the range of 70 to 150°C, more preferably 80 to 140°C, and particularly preferably 100 to 135°C. If the drying temperature is too low, drying may be insufficient, and the final wetlaid nonwoven fabric may lack strength. Conversely, if the drying temperature is too high, the undrawn yarn may crystallize, and the final wetlaid nonwoven fabric may lack strength.

[0045] After such wetlaid nonwoven fabrics are made by conventional methods, they are preferably heat-pressed by calendering to improve paper strength. Examples of calender rolls include metal / metal rolls, metal / paper rolls, and metal / elastic rolls. The pressing temperature is preferably within the range of 100 to 250°C, more preferably 150 to 250°C, and particularly preferably 160 to 230°C. If the temperature is too low, the fibers may not be crushed easily, and the wetlaid nonwoven fabric may not exhibit sufficient strength, which is undesirable. Conversely, if the temperature is too high, the fibers may melt easily, making it difficult to produce a uniform wetlaid nonwoven fabric. The pressing pressure is preferably within the range of 10 to 250 kgf / cm, more preferably 20 to 200 kgf / cm, and particularly preferably 30 to 150 kgf / cm.

[0046] The wetlaid nonwoven fabric for filters of the present invention has a basis weight of 30 to 400 g / m 2 It is essential that the thickness is 40 to 150 g / m 2 It is preferable that the density is in the range of 50 to 100 g / m 2If the basis weight is too small, the number of fibers in the nonwoven fabric is small, and the resin in the porous membrane tends to bleed through to the back. On the other hand, if the basis weight is too large, the weight of the final product, such as a filter, tends to increase and become difficult to handle.

[0047] The thickness of the nonwoven fabric is preferably 20 to 300 μm, more preferably 30 to 200 μm, and even more preferably 50 to 150 μm. If the thickness is too thin, the resin tends to bleed through to the back when coated. Conversely, if the thickness is too large, the product weight of the filter or the like increases, making it difficult to handle.

[0048] The breathability of nonwoven fabric is 0.01~50cc / cm 2 / sec. If the air permeability is too low, the impregnation property and filter performance of the porous membrane tend to decrease. Conversely, if the air permeability is too high, the resin tends to easily bleed through when applied to the film.

[0049] The nonwoven fabric preferably has a longitudinal tensile strength of 18 N / 15 mm or more, more preferably 20 N / 15 mm or more, and particularly preferably in the range of 21 to 30 N / 15 mm. If the tensile strength is too small, the strength to hold the filter is insufficient, which is undesirable.

[0050] The maximum peak height in the surface roughness of the nonwoven fabric is preferably 0.05 to 100 μm. If the maximum peak height is small and the surface is too smooth, the nonwoven fabric surface tends to inhibit the effect of the porous structure, resulting in reduced breathability or reduced impregnation of the porous membrane resin, leading to reduced processability. Conversely, if the maximum peak height is too large, the nonwoven fabric surface tends to have a lot of fluff, which can cause snags during coating when processed into a filter, resulting in poor membrane smoothness. Similarly, the arithmetic mean height in the surface roughness is preferably in the range of 0.01 to 50 μm, more preferably 0.05 to 30 μm, and particularly preferably 0.1 to 10 μm. The average height of the protruding peaks is preferably in the range of 0.05 to 7.0 μm, more preferably 0.5 to 6.0 μm, and particularly preferably 1.0 to 5.5 μm.

[0051] Such a wetlaid nonwoven fabric for a filter of the present invention can be made into a filter, which is another aspect of the present invention, by further forming a porous film on its surface. That is, another filter of the present invention is a filter comprising the above-mentioned wetlaid nonwoven fabric for filters of the present invention and a porous membrane present on the surface thereof.Furthermore, there is a method for producing a filter, comprising forming a porous membrane on the surface of the above-mentioned wetlaid nonwoven fabric for filters of the present invention.

[0052] In the present invention, the porous membrane present on the surface of the wetlaid nonwoven fabric is not particularly limited as long as it is used for filtering. Specific examples of such porous membranes include polysulfone (PS), polyarylethersulfone such as polyethersulfone (PES), polyimide, polyvinylidene fluoride (PVDF), and various other materials. Among these, porous layers made of polysulfone and polyarylethersulfone are preferred because of their chemical, mechanical, and thermal stability. Such porous layers preferably have a thickness of 10 to 150 μm.

[0053] In addition, when forming such a porous membrane, an aprotic solvent that dissolves the porous layer resin is usually used. Examples of aprotic solvents include organic polar amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, and N-methylcaprolactam, water-soluble ether compounds such as tetrahydrofuran and dioxane, water-soluble alcohol compounds such as methanol, ethanol, and ethylene glycol, water-soluble ketone compounds such as acetone and methyl ethyl ketone, and water-soluble nitrile compounds such as acetonitrile and propionitrile. These organic polar solvents may be used alone or as a mixed solvent of two or more.

[0054] In the method for producing the filter of the present invention, it is preferable to use an aprotic polar solvent when forming the porous membrane. In particular, the wetlaid nonwoven fabric for filters of the present invention is effective when N,N-dimethylformamide (hereinafter sometimes referred to as "DMF") is used as the aprotic solvent.

[0055] The porous film formed on the surface of the wetlaid nonwoven fabric is obtained by applying the above-mentioned coating liquid to the wetlaid nonwoven fabric in a certain thickness in a conventional manner, for example, by using a casting method, applying a film to a thickness of 50 to 500 μm on the wetlaid nonwoven fabric using an applicator or the like, and then immersing the film in a coagulation liquid to form a porous film.

[0056] In the filter of the present invention, the thickness of the porous membrane is preferably 300 μm or less, more preferably in the range of 10 to 250 μm, and particularly preferably 10 to 200 μm. If the thickness is too thick, the resistance to water permeation increases when used as a filter, and water permeation tends to be difficult.

[0057] Furthermore, the maximum peak height in the surface roughness of the porous membrane is preferably 0.05 to 10 μm. If the maximum peak height is too small, the porous membrane will have a smooth structure rather than a porous one, which tends to reduce the breathability and water permeability. If the maximum peak height is too high, the porous membrane will have many irregularities and tend to be less smooth. Similarly, the arithmetic mean height in the surface roughness is preferably in the range of 0.01 to 1.20 μm, more preferably 0.05 to 1.00 μm, and particularly preferably 0.10 to 0.90 μm. Furthermore, the average height of the protruding peaks is preferably in the range of 0.01 to 1.00 μm, more preferably 0.1 to 1.00 μm, and particularly preferably 0.5 to 1.00 μm.

[0058] Furthermore, in the filter of the present invention, it is preferable that the dimensional stability is in the range of 0.8 to 10. Here, dimensional stability is a numerical value indicating the state of the filter after coating a porous membrane on a wetlaid nonwoven fabric, and is calculated from the following formula using the change in shape of the coated porous membrane as an index. That is, the "equivalent volume" calculated from the height of the highest convex part of the concave-convex part of the porous membrane after coating is divided by the "volume" calculated from the average thickness of the porous membrane, and the "dimensional stability" is the value closer to 1.0. The less the concave-convex part of the porous membrane, that is, the less deformation of the wetlaid nonwoven fabric that serves as the base fabric, and the smoother the surface of the 20 cm square porous membrane, the closer the value is to 1.0. Dimensional stability = equivalent volume of porous membrane / volume of porous membrane Volume of porous membrane = Area of ​​20cm square sample × Average thickness of porous membrane (cm) Converted volume of porous membrane = area of ​​20cm square sample × maximum height of convex part of porous membrane (cm)

[0059] As mentioned above, in the method for producing the filter of the present invention, it is preferable to use an aprotic polar solvent when forming the porous membrane, but this aprotic polar solvent often damages synthetic fibers, particularly binder fibers. In the present invention, by selecting polyester unstretched staple fibers containing 2 to 18 mol% of isophthalic acid and / or sulfoisophthalic acid salt as the binder fiber, such damage is suppressed, and the wetlaid nonwoven fabric serving as the substrate is not damaged during the formation of the porous membrane, resulting in a filter with excellent dimensional stability. Furthermore, the filter of the present invention is preferably a membrane filter in which an aromatic polyamide layer is further formed on the porous membrane. [Example]

[0060] Examples will be given below to illustrate the configuration and effects of the present invention, but the present invention is not limited to these examples. The physical properties in the examples and comparative examples were measured according to the following methods.

[0061] (1) Intrinsic viscosity:[η] In the case of polyester fibers, 0.12 g of a fiber (polymer) sample was dissolved in 10 mL of a tetrachloroethane / phenol mixed solvent (volume ratio 1 / 1), and the intrinsic viscosity (dL / g) at 35°C was measured.

[0062] (2) Birefringence (Δn) Using a commercially available polarizing microscope and a sodium lamp as a light source, the retardation was calculated by the Berek compensator method under the condition that the sample was immersed in α-bromonaphthalene.

[0063] (3) Specific gravity The sample was placed in a density gradient tube (25°C) made of a mixed solvent of n-heptane and carbon tetrachloride, and the value after 6 hours was read as the specific gravity.

[0064] (4) Crystallization temperature Measurement was carried out using a commercially available differential scanning calorimeter (DSC) at a temperature rise rate of 10°C / min, and the endothermic peak temperature due to crystallization was taken as the crystallization temperature.

[0065] (5) Single yarn fineness Measurement was performed according to the method described in JIS L 1015:2010 8.5.1 Method B.

[0066] (6) Fiber length Measurement was performed according to the method described in JIS L 1015:2010 8.4.2 Method B.

[0067] (7) Solubility in aprotic polar solvents (solubility in DMF) 1 g of yarn was collected, its weight measured before immersion, and then it was immersed in 10 mL of aprotic polar solvent for 1 hour. The yarn was then removed, the excess aprotic polar solvent wiped off, and it was dried in a hot air dryer at 170°C for 1 hour, after which its weight was measured after immersion. The weight loss rate was calculated using the following formula. (Note that in the following experimental examples, DMF (N,N-dimethylformamide) was used as the aprotic polar solvent.) Weight reduction rate (%) = (Weight before immersion - Weight after immersion) / Weight before immersion × 100

[0068] (8) Metsuke Measurements were carried out in accordance with the weight per unit area test method of JIS L1906.

[0069] (9) Thickness Using a digital linear gauge DG-925 (Ono Sokki Co., Ltd.) (diameter of the measurement terminal: 1 cm), the thickness was measured at 20 randomly selected points, and the average value was calculated.

[0070] (10) Density The weight was calculated from the above basis weight and thickness using the following formula. Density (g / cm 3 ) = basis weight (g / m 2 ) ÷ thickness (μm)

[0071] (11) Tensile strength The tensile strength was measured based on JIS P8113 (Testing method for tensile properties of paper and paperboard).

[0072] (12) Breathability Measurement was carried out in accordance with the JIS L 1913 Frazier method.

[0073] (13) Surface roughness The surface roughness was measured using a laser microscope VK-X160 (manufactured by Keyence Corporation).

[0074] (14) Thickness and "volume" of the porous film of the sample after coating A cross-sectional photograph of the coated sample was taken using a scanning electron microscope SEM "JSM-6330F" (manufactured by JEOL Ltd.), and the thickness of the porous film was measured to obtain the average thickness of the porous film of the coated sample. The volume of the porous film of the sample after coating was calculated by the following formula. The volume of the porous film of the sample after coating (cm 3 ) (hereinafter referred to as "volume") = 20cm length x 20cm width x average thickness of sample after coating (cm)

[0075] (15) Height and "equivalent volume" of the sample after coating The coated sample was cut into a piece 20cm long x 20cm wide and placed on a flat plate. The height was measured with a ruler and the converted volume after coating was calculated. If the surface was uneven, the height was measured as the highest convex part. The converted volume of the porous film of the sample after coating was calculated using the following formula. The equivalent volume (cm) of the porous film of the sample after coating 3 ) (hereinafter referred to as "equivalent volume") = 20cm length x 20cm width x maximum height of the convex part of the porous film of the sample after coating (cm)

[0076] (16) Dimensional stability The dimensional stability was calculated using the following formula: "Dimensional stability" = "(porous membrane) converted volume" / "(porous membrane) volume"

[0077] Example 1 · Polyester unstretched staple fiber (binder fiber) Polyethylene terephthalate pellets copolymerized with 10 mol% isophthalic acid were melted at 280°C, extruded through a spinneret with 2504 holes at a throughput rate of 412 g / min, and taken up at a spinning speed of 1250 m / min to obtain unstretched polyethylene terephthalate fibers with a single filament fineness of 1.3 dtex. The polyethylene terephthalate fibers were formed into a tow of approximately 200,000 dtex, and after applying an oil, the tow was squeezed to a moisture content of approximately 15% by weight and cut to a length of 5 mm using a drum cutter to obtain unstretched polyethylene terephthalate staple fibers. Table 1 shows the production conditions and physical properties.

[0078] ·Wet nonwoven fabric The resulting unstretched polyethylene terephthalate staple fibers (40% by weight) and 60% by weight of stretched, heat-treated polyethylene terephthalate stretched fibers (0.6 dtex, 5 mm long) were dispersed in water and vigorously stirred in a mixer to form a slurry. The slurry was then transferred to a tapping paper machine, and a dispersant (DT-100, manufactured by Takamatsu Oil & Fat Co., Ltd.) was added to the slurry at 0.1% by mass and thoroughly stirred. The water was removed, and the resulting sheet was formed on a mesh and dried at 120°C using a rotary dryer to produce base paper. The resulting base paper was pressed at a linear pressure of 50 kgf / cm using a calendering device consisting of a combination of a metal roll and an elastic roll heated to 200°C to obtain a wet-laid nonwoven fabric. The physical properties of the resulting stretched fibers are shown in Table 1, and the physical properties of the nonwoven fabric are shown in Table 2.

[0079] Filters with porous membrane on the surface Polysulfone resin was weighed out so as to give a concentration of 8% by weight and added to DMF, and the mixture was stirred while maintaining the liquid temperature at 70°C to prepare a coating liquid. A wet polyester nonwoven fabric was placed on a glass plate, and the coating solution was dropped onto the nonwoven fabric using a 200 μm film thickness applicator. Immediately after coating, the nonwoven fabric was immersed in water and removed after 10 minutes to produce a filter with a porous membrane on its surface. No damage was observed on the wet nonwoven fabric due to the aprotic polar solvent (DMF). The physical properties of the obtained porous membrane etc. are shown in Table 3.

[0080] Example 2 Unstretched polyethylene terephthalate staple fibers were obtained in the same manner as in Example 1, except that the copolymerization amount of isophthalic acid was changed from 10 mol% in Example 1 to 15 mol%. Furthermore, using the unstretched staple fibers obtained, a wetlaid nonwoven fabric and a filter having a porous membrane on its surface were obtained in the same manner as in Example 1, except that the calendering temperature was changed to 190°C. No damage due to the aprotic polar solvent (DMF) was observed on the wetlaid nonwoven fabric. Tables 1 to 3 show the production conditions and physical properties.

[0081] Example 3 Unstretched polyethylene terephthalate staple fibers were obtained in the same manner as in Example 1, except that the copolymerization amount of isophthalic acid was changed from 10 mol% in Example 1 to 20 mol%. Furthermore, using the unstretched staple fibers obtained, a wetlaid nonwoven fabric and a filter having a porous membrane on its surface were obtained in the same manner as in Example 1, except that the calendering temperature was changed to 180°C. No damage due to the aprotic polar solvent (DMF) was observed on the wetlaid nonwoven fabric. Tables 1 to 3 show the production conditions and physical properties.

[0082] Example 4 Unstretched polyethylene terephthalate staple fibers were obtained in the same manner as in Example 1, except that the isophthalic acid in Example 1 was changed to sodium sulfoisophthalate and the copolymerization amount was 4.5 mol%. Furthermore, a wet-laid nonwoven fabric and a filter having a porous membrane on its surface were obtained in the same manner as in Example 1. No damage caused by the aprotic polar solvent (DMF) was observed in the wet-laid nonwoven fabric. Tables 1 to 3 show the production conditions and physical properties.

[0083] (Comparative Example 1) Unstretched polyethylene terephthalate short fibers were obtained in the same manner as in Example 1, except that no copolymerization component was used. The intrinsic viscosity of the polyethylene terephthalate pellets at this time was 0.63 dL / g. Furthermore, in the same manner as in Example 1, a wet-laid nonwoven fabric and a filter having a porous membrane on its surface were obtained. No damage due to the aprotic polar solvent (DMF) was observed in the wet-laid nonwoven fabric. Tables 1 to 3 show the production conditions and physical properties.

[0084] (Comparative Example 2) Unstretched polyethylene terephthalate staple fibers were obtained in the same manner as in Example 1, except that the copolymerization amount of isophthalic acid was changed from 10 mol% in Example 1 to 25 mol%. Furthermore, using the unstretched staple fibers obtained, a wetlaid nonwoven fabric and a filter having a porous membrane on its surface were obtained in the same manner as in Example 1, except that the calendering temperature was changed to 170°C. Damage caused by the aprotic polar solvent (DMF) was observed in the wetlaid nonwoven fabric. Tables 1 to 3 show the production conditions and physical properties.

[0085] [Table 1]

[0086] [Table 2]

[0087] [Table 3]

Claims

1. A wetlaid nonwoven fabric made of synthetic fibers, which contains polyester unstretched staple fibers containing 2 to 18 mol% of isophthalic acid and / or sulfoisophthalic acid salt, and has a basis weight of 30 to 400 g / m 2 A wet-laid nonwoven fabric for filters, characterized by:

2. 2. The wetlaid nonwoven fabric for filters according to claim 1, wherein the wetlaid nonwoven fabric comprises mainly drawn fibers.

3. 3. The wetlaid nonwoven fabric for filters according to claim 2, wherein the drawn fibers are polyester drawn fibers.

4. 2. The wetlaid nonwoven fabric for filters according to claim 1, wherein the maximum peak height in the surface roughness of the wetlaid nonwoven fabric is in the range of 0.05 to 100 μm.

5. A filter comprising the wetlaid nonwoven fabric for filters according to any one of claims 1 to 4 and a porous membrane present on the surface thereof.

6. 6. The filter according to claim 5, wherein the porous membrane is made of any one of polysulfone, polyethersulfone, and polyvinylidene fluoride.

7. The filter further has an aromatic polyamide layer on its surface.

8. A method for producing a filter, which comprises forming a porous membrane on the surface of the wetlaid nonwoven fabric for filters according to any one of claims 1 to 4.

9. A method for producing a filter using an aprotic polar solvent when forming a porous membrane.

Citation Information

Patent Citations

  • Separation membrane

    JP2001017842A

  • Non-woven fabric, separation membrane support, separation membrane, fluid separation element, and method for manufacturing non-woven fabric

    WO2015046215A1